1995
DOI: 10.1159/000106958
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Quantification of Alzheimer's Disease Severity: 'Time Index' Model

Abstract: A fundamental issue in the clinical and neuropathological assessment of Alzheimer''s disease patients is quantification of dementia severity progression. Several methods have been advanced for the purpose of staging dementia with various sensitivities at different phases of the disease, but no mathematical function has been developed to link these measures to a physical continuum. Using a dynamic method for quantifying illness severity, change in severity over time was referenced to a cumulative temporal index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 57 publications
(81 reference statements)
2
39
0
Order By: Relevance
“…Experimentally, exposing rat proximal tubular cells to cystine causes a decrease in solute reabsorption. This is associated with a fall in ATP levels and oxygen consumption, and more detailed analysis suggests inhibition of complex I (see figure 2) in the mitochondrial respiratory chain [25]. More recent work on primary cultures of human proximal tubular cells derived from urine has demonstrated that although mitochondria in cystinosis appear to function normally under baseline conditions, the levels of the important intracellular antioxidant agent glutathione are reduced.…”
Section: Renal Fs and Proximal Tubulopathymentioning
confidence: 99%
“…Experimentally, exposing rat proximal tubular cells to cystine causes a decrease in solute reabsorption. This is associated with a fall in ATP levels and oxygen consumption, and more detailed analysis suggests inhibition of complex I (see figure 2) in the mitochondrial respiratory chain [25]. More recent work on primary cultures of human proximal tubular cells derived from urine has demonstrated that although mitochondria in cystinosis appear to function normally under baseline conditions, the levels of the important intracellular antioxidant agent glutathione are reduced.…”
Section: Renal Fs and Proximal Tubulopathymentioning
confidence: 99%
“…By systematic combination, these multiple scales provide a 150-point dynamic range. GCS values were then translated into TI units [1]. Using TI units, the repeated measures over time clearly demonstrate the devastating progression of AD (Fig.…”
Section: Estimation Of Rate Of Dementia Progressionmentioning
confidence: 99%
“…Ashford et al [19], for example, note that among the range of patients they tested, there was a close correlation between the MMSE and the time-index form of assessment, such that the MMSE could explain 90% of the variance of the latter. Each such scale could also be used to define stages that would perform comparably to both the GDS and the MMSE staging.…”
Section: Clinical Practice and Research Issuesmentioning
confidence: 98%
“…The issue of more meaningful quantification of rate of decline has been discussed in depth by Ashford et al [19]. In this study they developed a 'time-index' model of severity of AD, thus also an interval scale.…”
Section: Measurement and Analytic Issues Related To Stagingmentioning
confidence: 99%
See 1 more Smart Citation